(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This paper will consider the practice of spiritual exercises – askésis – in antiquity and suggest that a revival of these ancient philosophical practices might support an applied form of existential psychotherapy, where psychotherapists’ own engagement with askésis enriches and deepens what they are able to offer their clients’ own enquiries.